A silica-based antioxidant nanoparticle for oral delivery of Camptothecin which reduces intestinal side effects while improving drug efficacy for colon cancer treatment. (15th April 2022) - Nguyen-Trinh, Quynh Nhu; Trinh, Kim Xuyen Thi; Trinh, Nhu-Thuy; Vo, Van Toi; Li, Nan; Nagasaki, Yukio; Vong, Long Binh
Abstract: Camptothecin (CPT) is a potent anticancer agent for the treatment of colorectal cancer; however, it exhibits some limitations, including poor solubility, low stability, and low bioavailability via oral administration, which restrict its usability in clinical treatments. In addition, overproduction of reactive oxygen species (ROS) during chemotherapy induces drug resistance and severe intestinal side effects. In this study, silica-installed ROS scavenging nanoparticles (siRNP) with 50–60 nm in diameter were employed to overcome the aforementioned drawbacks of CPT. The solubility of CPT was significantly improved by incorporating it into the core of the nanoparticle, forming CPT-loaded siRNP (CPT@siRNP). The anticancer activity of CPT@siRNP against colorectal cancer cells (C-26) in vitro was significantly improved as compared to free CPT through higher efficiency of intracellular internalization and induction of apoptosis. Owing to its antioxidant properties, CPT@siRNP reduced cytotoxicity to normal endothelial cells, which was in sharp contrast to the high toxicity of free CPT. Oral administration of CPT and CPT@siRNP to the C-26 tumor-bearing mice exhibited antitumor activity, accompanied by effective suppression of tumor growth. Although CPT treatment suppressed tumor progression, it caused severe side effects, including intestinal damage and significant bodyweight loss. Interestingly, such noticeable side effects were not observed in the mice treated with CPT@siRNP, and the effect of tumor growth inhibition tended to be similar to or higher than that of CPT treatment. The results obtained in this study indicate that CPT@siRNP is a potential therapeutic nanomedicine for the treatment of colon cancer. Statement of significance: Here we employed silica-containing antioxidant nanoparticle (siRNP) as promising oral delivery nanocarrier of campothecin (CPT) to treat colon cancer. The design of siRNP via covalent conjugation of antioxidant nitroxide radicals and the silanol groups in the polymer backbone contributes to a significant increase in the absorption of hydrophobic drug molecules inside the core and enhances the stability of nanoparticles in the gastrointestinal environment for oral drug delivery. CPT-loaded siRNP (CPT@siRNP) significantly improved solubility of CPT. As compared to free CTP, the CPT@siRNP treatment showed a significantly higher toxicity to colon cancer cell, inhibition of cancer cell migration, and induction of apopotosis. With the antioxidant feature, siRNP also significantly suppressed the intestinal side effects caused by CPT treatment in tumor-bearing mouse model. Graphical abstract: Image, graphical abstract